Effects of Pure Dzyaloshinskii–Moriya Interaction with Magnetic Field on Entanglement in Intrinsic Decoherence*Supported by the National Natural Science Foundation of China under Grant Nos 11204061, 11374085, 11104057, 11274010 and 11204002, the Anhui Provincial Natural Science Foundation under Grant No 1408085MA16, the Anhui Provincial Candidates for Academic and Technical Leaders Foundation under Grant No 2015H052, the Discipline Top-Notch Talents Foundation, the Excellent Young Talents Support Plan of Anhui Provincial Universities, the Specialized Research Fund for the Doctoral Program of Higher Education under Grant No 20113401110002, the 211 Project of Anhui University, and the Personnel Department of Anhui Province. (May 2016) - Li 李, Da-Chuang 大创; Wang 王, Xian-Ping 先萍; Li 李, Hu 虎; Li 李, Xiao-Man 小曼; Yang 杨, Ming 名; Cao 曹, Zhuo-Liang 卓良
Abstract : We investigate the effects of pure Dzyaloshinskii–Moriya (DM) interaction with magnetic field on entanglement in intrinsic decoherence, assuming that the system is initially in four Bell states | ϕ ± 〉 = ( | 00 〉 ± | 11 〉 ) / 2 and | ψ ± 〉 = ( | 01 〉 ± | 10 〉 ) / 2, respectively. It is found that if the system is initially in the state ρ 1 ( 0 ) = | ϕ + 〉 〈 ϕ + |, the entanglement can obtain its maximum when the DM interaction vectorD is in the plane of XOZ and magnetic fieldB =B y with the infinite time t, moreover the entanglement is independent of By and t whenB y is perpendicular toD . In addition, we obtain similar results when the system is initially in the states ρ 2 ( 0 ) = | ϕ - 〉 〈 ϕ - | or ρ 3 ( 0 ) = | ψ + 〉 〈 ψ + | . However, we find that if the system is initially in the state ρ 4 ( 0 ) = | ψ - 〉 〈 ψ - |, the entanglement can obtain its maximum for infinite t, when the DM vector is in the plane of YOZ, XOZ, or XOY, with the magnetic field parallel to X, Y, or Z axis, respectively. Moreover, when the axialB is perpendicular toD for the initial state ρ4 (0), the negativity oscillates with time t and reaches a stable value, the larger the value ofB is, the greater the stable value is, and the shorter the oscillation time of the negativity is. Thus we can adjust the direction and value of the external magnetic field to obtain the maximal entanglement, and avoid the adverse effects of external environment in some initial state. This is feasible within the current experimental technology.